The association between maternal HbA1c and adverse outcomes in gestational diabetes - Muhuza, Marie Parfaite Uwimana; Zhang, Lixia; Wu, Qi; Qi, Lu; Chen, Danqing; Liang, Zhaoxia (Frontiers in Endocrinology, 2023)
Background: The role of HbA1c in women with gestational diabetes mellitus (GDM) is still unclear, particularly in Asian population. Aim: To investigate the association between HbA1c levels and adverse outcomes in consideration of maternal age, pre-pregnancy body mass index (BMI), and gestational weight gain (GWG) in women with GDM. Method: A retrospective study included 2048 women with GDM and singleton live births. In multiple regression, association between HbA1c and adverse pregnancy outcomes were assessed. Result: Compared to HbA1c ≤ 5.0%, HbA1c ≥5.5% was significantly associated with macrosomia (aOR 2.63,95%CI1.61,4.31), PIH (aOR 2.56,95%CI1.57,4.19), preterm birth (aOR 1.64,95%CI 1.05,2.55), and primary C-section(aOR1.49,95%CI1.09,2.03). The association between HbA1c and adverse outcomes varied with maternal age, pre-pregnancy BMI, and GWG. Interestingly, pre-pregnant normal weight women with HbA1c ≥5.5% were significantly associated with increased risk of macrosomia, preterm birth, primary C-section, and PIH compared to their counterparts with HbA1c ≤5.0%. HbA1c≥5.5% was significantly associated with macrosomia among women with inadequate GWG or excess GWG compared to HbA1c≤ 5.0%. Interestingly, women with adequate GWG who had HbA1c ≥5.5% were significantly associated with PIH. Conclusion: Conclusively, HbA1c is significantly associated with macrosomia, preterm birth, PIH, and primary C-section in GDM women, particularly in women with HbA1c≥5.5%.